Food system actor perspectives on future-proofing European food systems through plant breeding - S. Stetkiewicz; J. Menary; A. Nair; M. Rufino; A. R. H. Fischer; M. Cornelissen; A. Guichaoua; P. Jorasch; S. Lemarié; A. K. Nanda; R. Wilhelm; J. A. C. Davies (Scientific Reports, 2023)
Abstract Crop improvement is a key innovation area in the pursuit of sustainable food systems. However, realising its potential requires integration of the needs and priorities of all agri-food chain stakeholders. In this study, we provide a multi-stakeholder perspective on the role of crop improvement in future-proofing the European food system. We engaged agri-business, farm- and consumer-level stakeholders, and plant scientists through an online survey and focus groups. Four of each group’s top five priorities were shared and related to environmental sustainability goals (water, nitrogen and phosphorus efficiency, and heat stress). Consensus was identified on issues including considering existing alternatives to plant breeding (e.g. management strategies), minimising trade-offs, and addressing geographical variation in needs. We conducted a rapid evidence synthesis on the impacts of priority crop improvement options, highlighting the urgent need for further research examining downstream sustainability impacts to identify concrete targets for plant breeding innovation as a food systems solution.